Green and Islamic Human Resource Management and Their Impact on Sustainability Performance: Evidence from Islamic Financial Institutions in Indonesia - Anis Nur Laili; Irma Yuliani; Izra Berakon (Falahiya Journal of Islamic Banking and Finance, 2026)
Introduction: This study aims to test and analyze the Integration of Green Human Resource Management (GHRM) and Islamic Human Resource Management (IHRM) in Supporting Sustainable Company Performance at Islamic Financial Institutions in Ponorogo, Indonesia. Research Methods: Data were collected by distributing questionnaires to a sample of 75 employees of Islamic Financial Institutions in Ponorogo, Indonesia. This study used Structural Equation Modeling – Partial Least Squares (SEM PLS) techniques to test and analyze data using SmartPLS 3. Results: The results indicate that there is a positive and significant influence between Green Human Resource Management (GHRM), Islamic Human Resource Management (IHRM), Top Management Support, and Green Motivation on Sustainability Performance in Islamic Financial Institutions in Ponorogo, Indonesia. Conclusion: This study provides practical insights for regulators and Islamic financial institutions to develop policies and strategies that integrate green and Islamic human resource management (HRM) practices. Recommendations include strengthening regulations on green finance, implementing sustainability reporting, and integrating Islamic and environmental values into HRM processes such as recruitment, training, and development.